Preclinical dosimetric evaluation of Ixolaris labeled with 99mTc and Translacional Model (Brazilian Journal of Radiation Sciences (BJRS), 2019)
ABSTRACT This study aimed to determine the biokinetic model for Ixolaris labelled with 99mTc radiotracer in mice by means of an imaging dosimetry method to estimate the absorbed and effective doses resulting from the diagnosis of melanoma and metastases in humans. C57BL6 mice induced animals with cell line B16-F10 murine melanoma were tested. It was determined by Single Photon Emission Tomography Computed (SPECT) images a latency period of 15 to 21 days for the development of lung metastasis in mice. The 99mTc-Ixolaris radiopharmaceutical was intravenously administered in a caudal vein, and SPECT images were acquired approximately at 0.5 h, 1.5 h, 2.5 h, 3.5 h and 24 h post-administration for analysis and biodistribution quantification. The biokinetic model was determined and cumulative activity to estimate the absorbed dose in each organ was calculated. The mass and metabolic differences between mice and humans were considered and used to extrapolate the data for different scales. Absorbed doses in irradiated target organs were calculated for the source organs based on dose factors provided by the software MIRDOSE and Olinda/EXM (S factor). Afterwards, the effective doses were estimated. The metabolic differences were 7,02 in this study. The dosimetric results indicated an estimated effective dose of 4.3 mSv for diagnostic exams conducted in human melanoma patients for an administered activity of 25.7 MBq. Comparing with effective doses resulting from other 99mTc diagnostic techniques, effective dose ranging from 0.6 to 4.8 mSv it was concluded that the procedure should proceed into a Clinical Phase in humans.